2020
DOI: 10.1021/jacs.0c04468
|View full text |Cite
|
Sign up to set email alerts
|

Direct Imaging of Correlated Defect Nanodomains in a Metal–Organic Framework

Abstract: Defect engineering can enhance key properties of metal–organic frameworks (MOFs). Tailoring the distribution of defects, for example in correlated nanodomains, requires characterization across length scales. However, a critical nanoscale characterization gap has emerged between the bulk diffraction techniques used to detect defect nanodomains and the subnanometer imaging used to observe individual defects. Here, we demonstrate that the emerging technique of scanning electron diffraction (SED) can bridge this g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 58 publications
(121 reference statements)
0
77
1
Order By: Relevance
“…For each duration of ball milling, 100 mg of activated MIL-100 was sealed inside a 10 mL stainless steel jar with one 7 mm diameter stainless steel ball bearing at room temperature. The jar was then placed in a Retsch MM400 grinder mill and ball milled at 25 Hz for 1,2,3,4,5,10,15 and 30 minute durations. After milling, the powder was recovered and characterised.…”
Section: Ball Millingmentioning
confidence: 99%
See 1 more Smart Citation
“…For each duration of ball milling, 100 mg of activated MIL-100 was sealed inside a 10 mL stainless steel jar with one 7 mm diameter stainless steel ball bearing at room temperature. The jar was then placed in a Retsch MM400 grinder mill and ball milled at 25 Hz for 1,2,3,4,5,10,15 and 30 minute durations. After milling, the powder was recovered and characterised.…”
Section: Ball Millingmentioning
confidence: 99%
“…For example, the modulated synthesis of UiO-66 is well documented to lead to the formation of correlated defect nanoregions. 9,10 Defects can also be introduced post-synthetically to a crystalline MOF, for example via post-synthetic linker exchange, which has been used to improve CO2 adsorption capacity in UiO-66. 11 Defects are often, inadvertently, incorporated into crystalline MOF powders when they are pressed into pellets to obtain the bulk materials that are commonly used in practical industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, such analyses often show small, or no significant, differences between HEAs and conventional alloys 19,20 . This study is based on coherent electron nanodiffraction, which was previously used for analyzing disorder in amorphous materials 21 . We report on how the observation and analysis of spatial fluctuations in diffuse scattering from a small volume of crystal, recorded using scanning electron nanodiffraction (SEND) [22][23][24] , can be applied for quantitative analysis and imaging of lattice distortion. For a wholistic insight from atomic mechanisms to the underlining nature of chemical disorder, we augment the diffraction study with aberration-corrected high-resolution electron microscopy (HREM) analysis and analytical transmission electron microscopy (TEM) determination of chemical inhomogeneity.…”
Section: Mainmentioning
confidence: 99%
“…Thus, the direct comparison of the results from the same area using the two detectors should provide a good test as to whether using direct electron detection provides significant advantages for SPED in one common application of this technique. It should be noted that this is just one way to process and use SPED data, and that recent work in scanned nanobeam electron diffraction and SPED has increasingly used open source libraries to process the data in a number of ways (Martineau et al, 2019;Sunde et al, 2019;Doherty et al, 2020;Johnstone et al, 2020aJohnstone et al, , 2020b, and that the advantages being investigated in this work would also provide advantages to such methods.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been demonstrated that scanned nanobeam electron diffraction using direct electron detectors gives high-quality, low noise data suitable for analyzing crystallography with nanometer resolution (Doherty et al, 2020; Johnstone et al, 2020 b ). It is therefore high time that SPED benefits from these advances in detectors in order to be able to reduce the noise and improve the pattern definition while operating at readout speeds even higher than those of video cameras.…”
Section: Introductionmentioning
confidence: 99%